Population Ageing in Ghana: Research Gaps and the Way Forward - Chuks J. Mba (Journal of Aging Research)
This paper attempts to highlight research gaps and what should be done concerning population ageing in the Ghanaian context. The proportion of the elderly increased from 4.9 percent in 1960 to 7.2 percent in 2000, while the number rose from 0.3 million to 1.4 million over the same period (an increase of 367 percent). Projection results indicate that by 2050, the aged population will account for 14.1 percent of the total population. Very little is known about the living arrangements and health profile of Ghana's older population. With increasing urbanization and modernization, it is important to know something about intergenerational transfers from adult children to their elderly parents, and characterize the elderly persons' food security strategies. Training of researchers will be important in terms of strengthening Ghana's capacity to monitor trends, as well as to conduct research and explore new directions in population ageing research.